Postobstructive Pulmonary Edema following Tonsillectomy/Adenoidectomy in a 2-Year-Old with Poland-Moebius Syndrome - Tanisha Powell; Nirupma Sharma; Kathleen T. McKie (Case Reports in Otolaryngology)
A 2-year-old male with Poland-Moebius syndrome was transferred from a local hospital to the Pediatric ICU at Children’s Hospital of Georgia for suspected postobstructive pulmonary edema (POPE) after tonsillectomy/adenoidectomy (T&A). The patient’s respiratory status ultimately declined and he developed respiratory failure. Imaging suggested pulmonary edema as well as a left-sided pneumonia. Echocardiogram showed pulmonary hypertension and airway exam via direct fiberoptic bronchoscopy revealed tracheomalacia and bronchomalacia. He developed acute respiratory distress syndrome (ARDS) and remained intubated for ten days. This case highlights the association between congenital upper body abnormalities with cranial nerve dysfunction and the development of POPE with delayed resolution of symptoms. Patients with upper body abnormalities as above are at great risk of postoperative complications and should therefore be managed in a tertiary-care facility.